Pengaruh Roa, Sales Growth, dan Current Ratio terhadap Financial Distress dengan Firm Size sebagai Pemoderasi: Pendekatan Regresi Data Panel - Wike Oktavia; Esi Fitriani Komara (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The main focus of this research is to identify and analyze the effects of ROA, sales growth, and current ratio on financial distress, as well as the role of firm size as a moderator. The analysis was conducted on business entities classified under the apparel and luxury goods subsector from 2019 to 2023, with the requirement that they be listed on the Indonesia Stock Exchange (IDX). This study employed quantitative methods, including descriptive analysis and associative relationships, with data obtained through documentation techniques by accessing information from the IDX's official website at www.idx.co.id. This research adopted panel data regression techniques with interaction testing using moderated regression analysis (MRA) assisted by EViews 12 software. A total of 12 companies were selected as sample units in this study, with 60 observations obtained through the application of purposive sampling techniques. Empirical findings reveal that ROA and current ratio can influence financial distress with a negative relationship, but sales growth has no impact. The three independent variables simultaneously contribute to financial distress. Meanwhile, firm size only reinforces the effect of return on assets on financial distress but fails to act as a moderator in the relationship between sales growth or current ratio to financial distress.